KERAMAHAN, KREDIBILITAS, CITRA KARYAWAN, KEPUASAN NASABAH DAN KEDEKATAN KARYAWAN DENGAN NASABAH, PENGARUHNYA TERHADAP LOYALITAS NASABAH PADA BANK BUMN DI SURABAYA - Dwi Setya Raharjo (Journal of Business & Banking, 2012)
It has been noted that any bank is always related to manage its customers with care. By doing so, the bank can get along with the high competition anywhere. Therefore, to be able to win in this competition, the bank requires existing. To do so, the bank must have a competitive advantage and be market oriented. It is not just for private banks, state-owned banks have to be so. Customers intimacy is a way of engaging with customers. Customers intimacy also encourages banks to create products on the market oriented. These studies tested the influence of elmployees benevolence, employees credibility, employees image, customers satisfaction and Customer Intimacy to Customer Loyalty. The study uses 125 respondents and these are analyzed by using SEM (Structural Equation Modeling) with Amos 18.0 program. Resutts of the study indicate a significant positive effect between variables employees image with customers intimacy, customers satisfaction with customers intimacy and customer intimacy with customers loyalty. On the other hand, there are two variables that have a positive effect is not significant that the employees benevolence with customer intimacy and employees cretlibility with customer intimacy.